PENGADAAN TANAH DALAM RANGKA PERCEPATANPEMBANGUNAN INFRASTRUKTUR KETENAGALISTRIKAN DALAM UPAYA MEWUJUDKAN PROYEK 35.000 MW - Manto Siregar; Aminuddin Salle; Sri Susyanti Nur (Faculty of Law, Universitas Riau, 2018)
This study aims to determine the procedure of land procurement and legal settlement mechanism against the rejection of land price and / or amount of compensation that has been set and implementation of acceleration process of land acquisition. This research employs empirical method of studying. The results of this study can be concluded that the procedure of land procurement and the stages of implementation starting from the planning stage, preparation stage, implementation phase, until delivery of the results, has been clearly regulated with the provisions of law applicable in Law number 2 of 2012 with all revisions the amendment of Presidential Decree Number 71 Year 2012 on Implementation of Land Procurement for Development for Public Interest. Mechanism of legal settlement against rejection of land price and / or amount of indemnification that has been set by the Appraisal team can be done with the step of applying for Custody of money payment of land compensation (consignment) to the local District Court.Keywords : Civil Law, Land Procurement, Public Interest